The role of the national education course in developing national values for Jordanian university students - Al-Qadey, Qamra Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the role of the national education course in developing the national values ​​of Jordanian university students from their point of view, and the study sample consisted of (350) students from Al-Balqa Applied University, who were selected from the students of the pre-education course for the national education. In the methodology of the study, a combination method was used (combining qualitative research in analyzing open questions and a descriptive survey approach in analyzing data). To achieve the goals of the study, a questionnaire consisting of (36) paragraphs was prepared, and two questions were answered, and the questionnaire enjoyed indications of honesty and acceptable stability. The results of the study indicated that the role of the national education course in developing the national values ​​of students came in a moderate degree, and students submitted (12) proposals to activate the role of the national education course in developing the national values ​​of students. Among the most important of these proposals is the interest in the religious and faith aspect of the content. The students have provided (9) additions to the national education course, the most important of which is the addition of a unit in the book related to citizenship in Islam. In light of the results of the study to activate the role of the national education course, the researcher recommends developing national values ​​for students by enriching the course with national values.